Thermal Degradation Mechanism of UV Curable Intumescent Flame Retardant Coating Based on Acryloyloxyethylneopentyl Phosphate - Liu, Yanyu; Liang, Hongbo; Xiong, Lei; Huang, Shengmei (Asian Journal of Chemistry, 2015)
In this work, series of UV curable intumescent flame retardants were prepared by blending acryloyloxyethylneopentyl phosphate with methacrylated phenolic melamine and pentaerythritol triacrylate. The thermal degradation mechanism of their cured films was studied by thermogravimetric analysis and in situ Fourier-transform infrared spectroscopy and a possible mechanism for the thermal degradation was proposed. The limiting oxygen index values of the cured films were measured. The expansion behaviors were also studied by unidirectional expansion degree. The results showed that the ANP/MAPM/PETA (35/25/40, wt/wt/wt) blend (ANP35MAPM25PETA40) had the best comprehensive properties among all the samples.